2023
DOI: 10.3389/fmars.2023.1052044
|View full text |Cite
|
Sign up to set email alerts
|

Structure and variability of the Pechora plume in the southeastern part of the Barents Sea

Abstract: The Pechora River forms the large Pechora River plume in the southeastern part of the Barents Sea (also called the Pechora Sea). Many previous works addressed water masses in the Barents Sea, however, the Pechora plume received relatively little attention, therefore, many basic aspects of its structure and variability remain unknown. In this study, we focus on spreading of the Pechora plume in the Pechora Sea during ice-free periods. Based on the extensive in situ measurements and satellite observations, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In general, long-term dynamics of the Pechora River discharge are characterised by two altering phases (Georgiadi and Groisman 2022): decreased flow (1936-1955; 1967-1980) and increased flow (1956-1966;1981-present) with difference of up to 500 m 3 s −1 (8-10 km 3 year −1 ) during freshet period, corresponding to less than 10% of total annual discharge. This is noticeably lower than interannual variability with the difference in maximum and minimum discharge in spring flood period between the consecutive years sometimes reaching 30-40 km 3 according to the analysis of multi-annual discharge data (Magritsky et al 2017;Rogozhin et al 2023). Overall, no significant changes in hydrological regime of the Pechora River have been reported in literature (Magritsky et al 2018;Frolova et al 2022).…”
Section: Hydrological Conditions In the Pechora Baymentioning
confidence: 84%
See 3 more Smart Citations
“…In general, long-term dynamics of the Pechora River discharge are characterised by two altering phases (Georgiadi and Groisman 2022): decreased flow (1936-1955; 1967-1980) and increased flow (1956-1966;1981-present) with difference of up to 500 m 3 s −1 (8-10 km 3 year −1 ) during freshet period, corresponding to less than 10% of total annual discharge. This is noticeably lower than interannual variability with the difference in maximum and minimum discharge in spring flood period between the consecutive years sometimes reaching 30-40 km 3 according to the analysis of multi-annual discharge data (Magritsky et al 2017;Rogozhin et al 2023). Overall, no significant changes in hydrological regime of the Pechora River have been reported in literature (Magritsky et al 2018;Frolova et al 2022).…”
Section: Hydrological Conditions In the Pechora Baymentioning
confidence: 84%
“…The lack of statistically significant differences between data from 1990s and 2020-2021 can be explained by a potentially high stability of estuarine macrozoobenthos, but also by the high spatial heterogeneity and interannual variability of macrozoobenthos in the area-to gain a better understanding of the temporal dynamics of macrozoobenthos in the context of ongoing climate change in the region, long-term timeseries data are essential. No significant changes were found in freshwater input during last decades (Magritsky et al 2017;Rogozhin et al 2023) to explain the lack of P. aestuariorum in the area, thus the nature of the disappearance of the previously common bivalve mollusc (Mosevich 1928) remains uncertain and requires further investigation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The hydrological conditions in the Kara Gate are influenced by the dynamics of the Pechora river plume and wind-driven currents. Recent studies revealed regular advection of the Pechora plume through the Kara Gate into the Kara Sea (Rogozhin et al, 2023). Pechora plume can act as a barrier from the south for microplastics coming from the Barents Sea and direct particles towards the Kara Gate or prevent the influx of MPs coming from Barents Sea.…”
Section: Kara Gatementioning
confidence: 99%